2015
DOI: 10.1002/bsl.2194
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Practice on Children's Ability to Apply Ground Rules in a Narrative Interview

Abstract: Despite the widespread use of ground rules in forensic interview guidelines, it is unknown whether children retain and apply these rules throughout narrative interviews. We evaluated the capacity of 260 five- to nine-year-olds to utilize three ground rules. At the beginning of the interview all children heard the rules; half also practiced them. Children then responded to open-ended prompts about a repeated laboratory event and were assessed for their application of the rules. Logistic regressions revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 48 publications
(76 reference statements)
2
42
1
Order By: Relevance
“…When specifically examining the "don't know" rule, however, only practice had an effect on children's usage of the rule (as opposed to simple delivery or no delivery at all). This finding is consistent with research involving nonAboriginal children, which has also found that the "don't know" ground rule needs to be practiced in order to be effective (Danby et al, 2015;Gee et al, 1999;Saywitz & Moan-Hardie, 1994). Some researchers have suggested that practicing rules consolidates children's memory of the rules as well as their confidence in using the rules (Righarts et al, 2013).…”
Section: Ground Rulessupporting
confidence: 88%
See 3 more Smart Citations
“…When specifically examining the "don't know" rule, however, only practice had an effect on children's usage of the rule (as opposed to simple delivery or no delivery at all). This finding is consistent with research involving nonAboriginal children, which has also found that the "don't know" ground rule needs to be practiced in order to be effective (Danby et al, 2015;Gee et al, 1999;Saywitz & Moan-Hardie, 1994). Some researchers have suggested that practicing rules consolidates children's memory of the rules as well as their confidence in using the rules (Righarts et al, 2013).…”
Section: Ground Rulessupporting
confidence: 88%
“…In line with the first hypothesis and previous research, the overall delivery and practice of ground rules at the beginning of the interview was positively associated with the spontaneous usage of rules in children's narratives of abuse (Danby et al, 2015;see Brubacher et al, 2015, for a review). When specifically examining the "don't know" rule, however, only practice had an effect on children's usage of the rule (as opposed to simple delivery or no delivery at all).…”
Section: Ground Rulessupporting
confidence: 68%
See 2 more Smart Citations
“…However, experimental studies have also shown that pre‐interview instructions encouraging children to say “I don't know” when they did not know led them to say “I don't know” appropriately more often, but the instruction did not affect responses to non‐misleading questions (Mulder & Vrij, ; Waterman & Blades, ). This was particularly true when children practiced using the “don't know” ground rule prior to substantive questioning (Danby, Brubacher, Sharman, & Powell, ). Such findings have informed recommendations that forensic interviewers should explicitly encourage children to say “I don't know/remember” when appropriate (Lamb et al, ).…”
Section: Experimental Research On Children's Uncertain Responsesmentioning
confidence: 99%